Estudo de metodologia analítica para a determinação do cetoconazol em formulações farmacêuticas - Santos, Jean Leandrodos [UNESP]; Ribeiro, Y. A. [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Chin, Chung Man [UNESP] (My University, 2009)
Ketoconazole is a synthetic broad-spectrum oral and topical antifungal drug derived from imidazole, effective in the treatment of superficial mycoses and systemic infections. In this study we have tested several methods to analyze ketoconazole in various pharmaceutical products containing this drug, employing techniques such as UV and IR spectrophotometry and thermal analysis. The results showed that UV spectrophotometry is a fast, practical and economical method and indicated that other methods, such as IR spectrophotometry and thermal analysis, could be good alternative methods for ketoconazole analysis in certain pharmaceutical forms.
Study of analytical methodology for ketoconazole determination in pharmaceutical preparation
Keywords: Analytical methods; Antifungal; Ketoconazole; Spectrophotometric analysis; Thermal analysis; ketoconazole; analytic method; drug determination; drug dosage form; infrared spectrophotometry; thermal analysis; ultraviolet spectrophotometry